Business-Process Approach to Economic Security Management of the Enterprises with Attraction of the Equation of Profitability - Alexander Ivanovich Kirjanen (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with topical issues of ensuring the financial stability of the organization on the basis of the unity of all aspects of business. The authors consider the mathematical model of profitability of financial flows of the company. The relationship between the equation of profitability of the company’s financial flows and the capital circulation equation, developed by K. Marx is held. The analysis of these equations is given. The role of the time factor in economic activity is shown.